Parameterized Two‐Qubit Gates for Enhanced Variational Quantum Eigensolver - Rasmussen, Stig Elkjær; Zinner, Nikolaj Thomas (Annalen der Physik, 2022)
The variational quantum eigensolver is a prominent hybrid quantum‐classical algorithm expected to impact near‐term quantum devices. They are usually based on a circuit ansatz consisting of parameterized single‐qubit gates and fixed two‐qubit gates. The effect of parameterized two‐qubit gates in the variational quantum eigensolver is studied. A variational quantum eigensolver algorithm is simulated using fixed and parameterized two‐qubit gates in the circuit ansatz and it is shown that the parameterized versions outperform the fixed versions, both when it comes to best energy and reducing outliers, for a range of Hamiltonians with applications in quantum chemistry and materials science. The parameterized quantum circuit used in variational quantum algorithms usually consists of parameterized single‐qubit gates and fixed entangling multi‐qubit gates. Here, it is considered what happens when the entangling gates become parameterized, which allows for directly tuning the entangling power of the circuit. The parameterized entangling gates are shown to outperform the fixed versions.